2012
DOI: 10.3109/02713683.2011.637656
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Osmolar Modification for Transepithelial Corneal Cross-Linking

Abstract: The transepithelial riboflavin solution should contain no dextran, but it should include 0.01% BAC and 0.44% NaCl to promote the permeability of riboflavin through the epithelium, resulting in a sufficient concentration of riboflavin in the corneal stroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 32 publications
1
56
0
3
Order By: Relevance
“…The use of BAC in rabbit eyes was shown to increase the riboflavin absorption coefficient through an intact epithelium. Nevertheless, the absorption coefficient achieved was only 37% that of epi-off absorption [74]. Slightly different results were shown in a very similar study, where the addition of BAC increased the riboflavin absorption coefficient in epi-on CXL to a level similar to a standard epi-off CXL.…”
Section: Evolution Of Riboflavin: Uva Corneal Collagen Crosslinkingmentioning
confidence: 66%
“…The use of BAC in rabbit eyes was shown to increase the riboflavin absorption coefficient through an intact epithelium. Nevertheless, the absorption coefficient achieved was only 37% that of epi-off absorption [74]. Slightly different results were shown in a very similar study, where the addition of BAC increased the riboflavin absorption coefficient in epi-on CXL to a level similar to a standard epi-off CXL.…”
Section: Evolution Of Riboflavin: Uva Corneal Collagen Crosslinkingmentioning
confidence: 66%
“…. Experimental comparative studies in rabbit corneas have shown that CXL of corneas with an intact epithelium using BAC 0.0005% results in an increase in biomechanical rigidity (Young's modulus) of about one-fifth of that induced by standard CXL with epithelial debridement 58 . This is presumably due to limited riboflavin absorption 59 .…”
Section: Technique Modifications Trans -Epithelial Cross-linking (Te mentioning
confidence: 99%
“…[18][19][20][21] Thus, there are valid reasons for seeking to modify the standard protocol and to perform the treatment with epithelial retention (''epi-ON'' protocols). [22][23][24] Early attempts to accomplish this have included the use of multiple applications of the topical anesthetic, tetracaine 1%, 25,26 20% ethanol solution, 27 0.02% benzalkonium chloride (BAC), 28 0.44% NaCl in combination with 0.01% BAC, 29 or by removing the epithelium in a grid pattern rather than complete debridement 27 to assist the diffusion of RF into the stroma before beginning the irradiation with UVA.…”
Section: Purposementioning
confidence: 99%